Coexistence is Communication: Heidegger’s Rhetorical View of Community - Wu, Roberto (Sofia, 2024)
Basic Concepts of Aristotelian Philosophy, written in 1924, is Heidegger’s only text entirely devoted to rhetoric. Therefore, it reveals to be a main source that express the link between language and community at the time of his project of hermeneutics of facticity. Similarities and differences concerning Being and Time conceptions make possible understanding the singularity of those concepts in his earlier work. The article especially explores the implication of the discursive modes of speaking and hearing in the formation of a communitarian bond.